Group Analysis of Official Hotel Classification Systems: A Recent Study - Vagena, Akrivi; Manoussakis, Gerassimos (Current Approaches in Science and Technology Research Vol. 4, 2021)
The present research investigates the official classification systems in order to find common, important sectors and criteria. Some criteria indicate the perception of certifying organizations, of countries that apply them, and of the hotel industry, as to what is important for a hotel to offer. Official classification systems state their basic principles, which differ from one system to another and not all are met at the same time. Most countries give three reasons for entering a formal rating system: consumer protection, tourism planning and marketing. The study will present the practices applied in the hotel industry, through compliance with official classification systems. It will contribute to the existing knowledge of hoteliers, institutions and organizations that create hotel certification systems, and in general to the knowledge of the tourism industry. Hotel classification systems are tools for maintaining the high quality of hotel industry. Also, ?he classification of hotels presents heterogeneity. Common points are the range of ranking categories and the marks used, but if the requirements of the criteria of each category are analyzed, very different conditions are discovered, sometimes even within the same country. Nevertheless, the introduction of a classification system for hotels is a complex matter due to the diversity of classification systems, accommodation types and the cultural, environmental and economic context in which the systems operate each time in individual countries. This study results, in a proposed model hotel classification system, which will directly contribute to reducing the risk of not meeting customers' expectations and providing hotel services more efficiently, depending on the type and category of accommodation. Effective management of customer expectations is crucial to ensuring the viability of the tourism business. The survey data were drawn from the analytical recording and processing of 39 classification systems, applied in different countries and continents.